A phylo-functional core of gut microbiota in healthy young Chinese cohorts across lifestyles, geography and ethnicities - Zhang, Jiachao; Guo, Zhuang; Xue, Zhengsheng; Sun, Zhihong; Zhang, Menghui; Wang, Lifeng; Wang, Guoyang; Wang, Fang; Xu, Jie; Cao, Hongfang; Xu, Haiyan; Lv, Qiang; et al. (The ISME Journal, 2015)
Structural profiling of healthy human gut microbiota across heterogeneous populations is necessary for benchmarking and characterizing the potential ecosystem services provided by particular gut symbionts for maintaining the health of their hosts. Here we performed a large structural survey of fecal microbiota in 314 healthy young adults, covering 20 rural and urban cohorts from 7 ethnic groups living in 9 provinces throughout China. Canonical analysis of unweighted UniFrac principal coordinates clustered the subjects mainly by their ethnicities/geography and less so by lifestyles. Nine predominant genera, all of which are known to contain short-chain fatty acid producers, co-occurred in all individuals and collectively represented nearly half of the total sequences. Interestingly, species-level compositional profiles within these nine genera still discriminated the subjects according to their ethnicities/geography and lifestyles. Therefore, a phylogenetically diverse core of gut microbiota at the genus level may be commonly shared by distinctive healthy populations as functionally indispensable ecosystem service providers for the hosts.